Vapour-Phase and Solid-Phase Epitaxy of Silicon on Solid-Phase Crystallised Seed Layers for Solar Cells Application - Wei Li; Sergey Varlamov; Miga Jung; Jialiang Huang (International Journal of Photoenergy)
Vapour-phase and solid-phase epitaxy are used for thickening of a solid-phase crystallised silicon seed layer on glass. Cross-sectional transmission microscope images confirm that a transfer of crystallographic information has taken place from the seed layer into the epilayers. X-ray diffraction, scanning electron microscopy, and transmission electron microscopy reveal that the density of planar defects (mainly on {111} plains) in the vapour-phase epitaxial sample is much higher than in the solid-phase epitaxial sample. These planar defects can act as recombination centres for free-charge carriers. Consequently, PC1D modelled minority carrier diffusion length in the vapour-phase grown epilayer is 50% shorter than that in the solid-phase grown epilayer. As a result, a solar cell grown by solid-phase epitaxy achieves open circuit voltage of 468 mV, short circuit current of 9.17 mA/cm2, and photovoltaic conversion efficiency at 2.75% which are all higher than those of the solar cell grown by vapour-phase epitaxy on the same seed layer, 400 mV, 7.28 mA/cm2, 1.69%, respectively. It proves that solid-phase epitaxy is more suitable for the solar cell growth on the solid-phase crystallised silicon seed layer than vapour-phase epitaxy.